Violence in the city that belongs to no one: urban distinctiveness and interconnected insecurities in Nairobi (Kenya). Issue 4 (4th July 2019) - Elfversson, Emma; Höglund, Kristine
ABSTRACT: Rapid urbanisation in the global South has prompted attention to the causes and dynamics of urban violence. Yet, much research tends to either analyse urban violence without attention to the broader conflict complexes of which it forms a part, neglecting linkages between different forms of urban violence and between urban and rural dynamics, or conversely study violence in cities without acknowledging the particularities of the urban context. In this article, we conceptualise urban violence, theorise how it is shaped by urban dynamics and explore its manifestations in Nairobi, Kenya. We find that while Nairobi is not uniquely violent inside Kenya, violence takes on distinct urban forms given city-level processes, and also that urban violence has led to policies that increase securitisation and militarisation of the city. Our analysis thus improves knowledge of how criminal and political violence is shaped by and shapes the stability of developing cities.